2009
DOI: 10.1097/hjh.0b013e328319917e
|View full text |Cite
|
Sign up to set email alerts
|

Poor adherence to home blood pressure measurement schedule

Abstract: In spite of the use of memory-equipped devices, to ensure patients' adherence to measurement schedules, patients still need proper instruction and a close watch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…23 In real-life clinical practice, adherence to measurements may not be as good as observed in our study, as demonstrated previously. 23,24 However, it is also possible that adherence could be even better in the real-life doctor-patient relationship. In any case, we feel that home BP should be measured twice, instead of once, on each occasion because of a lower number of required measurement days, a slightly better predictive ability, and the regression to the mean effect.…”
Section: Discussionmentioning
confidence: 99%
“…23 In real-life clinical practice, adherence to measurements may not be as good as observed in our study, as demonstrated previously. 23,24 However, it is also possible that adherence could be even better in the real-life doctor-patient relationship. In any case, we feel that home BP should be measured twice, instead of once, on each occasion because of a lower number of required measurement days, a slightly better predictive ability, and the regression to the mean effect.…”
Section: Discussionmentioning
confidence: 99%
“…9 With home blood pressure monitoring, patients are reported to be noncompliant with measurements or self-report of blood pressures. 10 There is a small but growing body of evidence to support a new method of offi ce measurements in which a series of automated measurements is taken with the patient sitting alone in a quiet room (serial automated OBPM). The scarce, available research comes predominantly from one research group that used a validated oscillometric offi ce blood pressure device able to be set at measurement intervals of 1 minute or more for a duration of 5 to 10 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…However, Van der Hoeven et al 18 studied 106 patients undergoing HBPM and concluded that they need proper instruction and a close watch. The authors verified that even using memory-equipped devices to ensure the accuracy of date, time and number of measurements, the participants had difficulties with the method 18 .…”
Section: Discussionmentioning
confidence: 99%